AN EXTENSIVE INSPECTION OF THE FORKLIFT FB25-77 IN THE MANUFACTURING SECTOR BASED ON INDONESIAN MINISTRY OF LABOUR REGULATION - Mutiarani Mutiarani; Rahman Hakim; Lalu Giat Juangsa Putra; Oriza Satifa (Jurnal Ilmiah Teknologi dan Rekayasa, 2024)
Workplace accidents can arise from various factors such as human elements, environmental conditions, equipment, machinery, work processes, the nature of tasks, and work methodologies. Forklifts which is classified under lifting and transporting equipment, are frequently utilized in industrial settings for material movement. To mitigate the risk of work-related accidents and ensure the safety and suitability of a forklift for operational use, a systematic inspection and testing process are essential. Typically conducted at regular intervals, every two years, and annually for regular use, this process assesses various aspects of lift and transport equipment, including forklifts. This study aims to evaluate the conformity of the examination results for a FB25-77 type forklift with the standards outlined in Minister of Manpower Regulation No. 8 of 2020. Employing a descriptive analysis method, the study involves comparing the actual condition of forklifts in the field against all the specified requirements in Permenaker No. 8 of 2020, encompassing visual inspection of construction, dimensional measurements, non-destructive testing (NDT), functional testing, and load testing. Based on the comprehensive inspection and testing procedures, it was ascertained that the equipment meets the Occupational Health and Safety (OHS) requirements, thereby warranting the issuance of a certificate by the Provincial Manpower Service.